Fungal diversity in set-aide agricultural soil investigated using terminal-restriction fragment length polymorphism - Klamer, Morten; Hedlund, Katarina (Soil biology & biochemistry, 2004)
As part of the restoration of biodiversity on former agricultural land there has been focused on methods to enhance the rate of transition from agricultural land towards natural grasslands or forest ecosystems. Management practices such as sowing seed mixtures and inoculating soil of later successional stages have been used. The aim of this study was to determine the effects of a managed plant community on the diversity of soil fungi in a newly abandoned agricultural land. A field site was set up consisting of 20 plots where the plant diversity was managed by either sowing 15 plant species, or natural colonization was allowed to occur. The plant mixture contained five species each of grasses, legumes and forbs that all were expected to occur at the site. A subset of the plots (five from each treatment) was inoculated with soil cores from a late successional stage. The plant community composition was subject to a principal component analysis based on the coverage of each species. Five years after abandonment, soil samples were taken from the plots, DNA was extracted and the ITS region of the rDNA gene was amplified using fluorescently labelled fungal specific primers (ITS 1F/ITS 4). The PCR products were digested using HinfI and TaqI and sequenced. Results from both restriction enzymes were combined and a principal component analysis performed on the presence/absence of fragments. Also the fungal diversity expressed as number of restriction fragments were analysed. There was significantly higher fungal species richness in the experimental plots compared to the forest and field soils, but no differences between sown and naturally colonized plots. The different plant treatments did not influence the below ground fungal community composition. Soil water content on the other hand had an impact on the fungal community composition.